Analysis of Physical Fitness Levels in Urban and Rural Klaten Students - Ubaidillah Kamal; Agus Darmawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Physical fitness is one of the key factors supporting the health, growth, and learning ability of elementary school students. Differences in environmental characteristics between urban and rural areas are thought to influence students’ physical fitness levels. This study aims to compare the physical fitness levels of elementary school students in urban and rural areas of Klaten Regency. The study employed a survey method using a comparative quantitative approach. The sample consisted of 89 male and female students with an average age of 11 years, selected using purposive sampling, comprising 48 students from SD Muhammadiyah 1 Tonggalan and 41 students from SDIT Persada Bayat. Data collection was conducted on April 20–24, 2026, using the Indonesian Physical Fitness Test (TKJI) for ages 11–12, which included a 40-meter run, 30-second sit-ups, 30- second sit-to-stand, standing long jump, and a 600-meter run. Data were analyzed using descriptive statistics and the Independent Samples t-test after meeting the normality and homogeneity tests. The results showed no significant differences in the bent arm hang, sit-up, and vertical jump components. However, there were significant differences in the 40-meter run and 600-meter run components. Urban students demonstrated better performance in the speed component, while rural students performed better in the cardiorespiratory endurance component. These findings suggest that environmental characteristics have the potential to influence specific physical fitness components in elementary school students.